Can Macroinvertebrate Traits Be Explored and Applied in Biomonitoring Riverine Systems Draining Forested Catchments? - Edegbene, Augustine O.; Arimoro, Francis O.; Odume, Oghenekaro N.; Ogidiaka, Efe; Keke, Unique N. (Frontiers in Water, 2021)
Trait-based approach (TBA) in recent time has received tremendous attention as complementary tool over taxonomic-based approach in assessing ecological health of riverine systems in developed countries, but in the Afrotropical region the trait-based approach is still in its infancy. No trait-based approach has been developed for riverine systems draining forested catchment in the Afrotropical region. Hence, this study was conducted to explore and apply macroinvertebrates traits as potential biomonitoring tools in assessing ecological health of riverine systems draining forested catchments in the Niger Delta area of Nigeria. Selected physico-chemical variables were sampled together with macroinvertebrates in 18 stations of 10 riverine systems from 2008 to 2012. The 18 stations were classified into three ecological classes namely near natural stations (NNS), slightly disturbed stations (SDS), and moderately disturbed stations (MDS) using physico-chemical-based classification with the aid of principal component analysis (PCA). The results revealed traits such as possessions of hardshell body armouring, preferences for clear and transparent water and opaque water, climbing and crawling mobility mechanisms, large (>20–40 mm) body size, preferences for scrapping, shredding, and grazing feeding habits to be associated with NNS and SDS based on RLQ (R, physico-chemical variables; L, taxa; Q, traits) analysis performed. Thus, these traits were deemed to be sensitive to human impact in forested systems. Also, traits such as tegument/cutaneous respiration, soft and exposed body armouring, burrowing mobility mechanism, spherical body shape, preference for detritus [fine particulate organic materials (FPOM)] food materials, small (>5–10 mm) body size and preference for filter feeding mechanism were associated with MDS. Hence, they were deemed tolerant of human impact in forested systems. A fourth-corner test performed revealed tegumental/cutaneous respiration preference, soft and exposed body armouring and burrowing mobility mode, which were associated with the MDS on the RLQ ordination were also positively correlated to 5 day biochemical oxygen demand (BOD5); while preference for clear and transparent water, which were positively associated with MDS, were also positively correlated with pH and negatively correlated to dissolved oxygen (DO). Overall, this study affirmed that the TBA can be explored in biomonitoring riverine systems draining forested catchments. Nevertheless, we suggest the trait-based approach to be further explored, with a view to developing trait-informed indices for biomonitoring Afrotropical riverine systems.